Consumer Debt and Over-Indebtedness in Times of COVID-19 - Überblick (Wirtschaftsdienst)
Abstract Consumer debt and over-indebtedness restrict financial self-determination. It is the task of the state to ensure that a minimum level of self-determination is guaranteed even in a pandemic. What is the minimum level? What is the responsibility of a consumer policy that dovetails with economic and social policy? Eighty participants from academia, consumer protection, social associations, business and ministries discussed three topics on 16 December, 2021 at the invitation of the German Council of Consumer Experts: 1) concepts, developments, causes of consumer indebtedness and over-indebtedness; 2) their social context; and 3) measures to secure economic self-determination.